Copy number variation and association studies - Conrad, Don (Henry Stewart Talks, 2008)
Background on copy number variation biology, Preprocessing and normalization of array data, QC techniques for CNV data, CNV discovery, Impact of differential bias on CNV associations, Methods for testing common CNVs in association studies, Methods for testing rare CNVs in association studies
Archived at 2021/02/25